Are climate restricted areas a viable interim climate mitigation option over the north atlantic? - Niklaß, Malte; Dahlmann, Katrin; Frömming, Christine; Grewe, Volker; Gollnick, Volker; Lührs, Benjamin; van Manen, J. (2016)
In order to achieve global environmental goals like the 2-degree-target, as well as to reduce longer-term emission levels, mitigation measures have to be introduced, preferably as early as possible. In aviation, the implementation of the most promising mitigation strategies, e.g. climate optimized routing, is linked with several technical challenges. An early introduction of interim mitigation strategies, which bridges the time period until most auspicious approaches reach market maturity, may pave the way for a prompt reduction of aviation’s induced global warming. Within this study, climate restricted airspaces (CRA) are defined in analogy to military exclusion zones. Climate cost functions (CCF) characterize the environmental impact caused by an aircraft emission at a certain location and time. To estimate the monthly climate sensitivity of an area, CCFs are derived with the climate-response model AirClim. Within this study, we close regions with climate sensitivities greater than a threshold value for a period of time (e.g. a month) and affected flight trajectories are re-routed cost optimally around them. The evaluation of the climate impact mitigation potential of climate restricted areas is performed based on optimal control techniques. Monetary costs are integrated into the cost functional of the Trajectory Optimization Module (TOM). Further, high penalties are introduced within restricted airspaces in order to ensure the avoidance of CRA. The cost-benefit potential (climate impact mitigation vs. rise in operating costs) for this interim mitigation concept is investigated for varying threshold values for the closure of airspace and compared with climate optimized trajectories (COT) for different routes and seasons of the year.